Processing of lignin in urea–zinc chloride deep-eutectic solvent and its use as a filler in a phenol-formaldehyde resin1. Issue 36 (23rd April 2015) - Lian, H.; Hong, S.; Carranza, A.; Mota-Morales, J. D.; Pojman, J. A.
<x xml:space="preserve">Abstract</x> The main goal of our research deals with a new greener and more efficient lignin modification method to optimize its structural performance as a phenol-formaldehyde resin filler.